Role of Calcium in Phosphatidylserine Externalisation in Red Blood Cells from Sickle Cell Patients - Erwin Weiss; David Charles Rees; John Stanley Gibson (Anemia)
Phosphatidylserine exposure occurs in red blood cells (RBCs) from sickle cell disease (SCD) patients and is increased by deoxygenation. The mechanisms responsible remain unclear. RBCs from SCD patients also have elevated cation permeability, and, in particular, a deoxygenation-induced cation conductance which mediates Ca2+ entry, providing an obvious link with phosphatidylserine exposure. The role of Ca2+ was investigated using FITC-labelled annexin. Results confirmed high phosphatidylserine exposure in RBCs from SCD patients increasing upon deoxygenation. When deoxygenated, phosphatidylserine exposure was further elevated as extracellular [Ca2+] was increased. This effect was inhibited by dipyridamole, intracellular Ca2+ chelation, and Gardos channel inhibition. Phosphatidylserine exposure was reduced in high K+ saline. Ca2+ levels required to elicit phosphatidylserine exposure were in the low micromolar range. Findings are consistent with Ca2+ entry through the deoxygenation-induced pathway (Psickle), activating the Gardos channel. [Ca2+] required for phosphatidylserine scrambling are in the range achievable in vivo.